Creativity and 'new' careers: what can we learn from the creative industries? - Bennett, Dawn (Black Swan Press-Curtin University of Technology, 2009)
The term "creative industries" generally refers to sectors of the economy that utilise individual creativity, skill and talent to create, produce and commercialise cultural goods and services. Given the general debate about innovation and creativity, it is useful to consider how the creativity, skills and talents that drive the creative industries might be applicable and useful to the general economy. This paper draws upon the adventures of a virtual musician to illustrate the broad range of skills and attributes employed by creative industry practitioners. Findings suggest strong alignment of these skills with the critical skills shortages identified by Australian businesses as impeding Australia's innovative ability. The potential for creatives to relieve these skilled labour shortages is largely unrealised.